Discovery of phloridzin as a new antagonist for Di(2-ethylhexyl) phthalate-induced male reproductive toxicity based on the adverse outcome pathway network and drug-target gene set enrichment analysis - Huan Gao; Xue Zhang; Ziqi Liu; Xiaoge Yang; Yajie Li; Mengxing Cui; Han Wang; Xiaoyu Chen; Weiying Zhang; Zhihan Liu; Yongjiang Yu; Liping Chen; et al. (Ecotoxicology and Environmental Safety)
Di(2-ethylhexyl) phthalate (DEHP) is a widespread ubiquitous phthalate environmental contaminant. The male reproductive toxicity (MRT) from exposure to DEHP and its main metabolite, mono(2-ethylhexyl) phthalate (MEHP), has been well documented. Fully elucidating its toxic mechanism and discovering effective antagonists are desirable means to reduce the health risks of DEHP. In this study, 552 genes related to MRT induced by DEHP/MEHP were screened out from the Comparative Toxicogenomics Database (CTD) and DisGeNET database. Next, we developed a global adverse outcome pathway (AOP) network based on the existed AOP-wiki. After functional enrichment analyses and mapping to the global AOP network, we found that the increased ROS level, cell cycle arrest, and increased apoptosis are key events (KEs) involved in DEHP-mediated MRT, which was validated in TM3 Leydig cell model. Among them, cellular apoptosis is the core KE in DEHP-induced MRT via network topological analysis. Eventually, we developed a novel in silico antagonist screening platform (http://43.136.69.224:3838/wlab/) based on drug-target gene set enrichment analysis (dtGSEA version 2.0). Several potential candidates that mitigate DEHP-mediated cellular apoptosis have been screened out, including quercetin, taurine, methionine, and phloridzin. Further experimental results demonstrated that phloridzin provided the most effective protection against MEHP-induced apoptosis in TM3 cells probably through the p53 and MAPK signaling pathways. Molecular docking and molecular dynamics simulations suggest that STAT3 and RUNX1 may be important targets for phloridzin to antagonize MEHP-induced MRT. Our study provides a new approach to discover the antagonists for the toxicity of environmental contaminants based on AOP network and dtGSEA methods.